Being A Young Scientist : Does Guided Inquiry Affect Students’ Scientific Literacy Skills? - Dhani, Arini Rahma; Agustinah, Agustinah (Faculty of Education Universitas Negeri Malang, 2023)
Guided inquiry learning encourages students to be more active in learning so that students' scientific literacy skills can be developed. Solving problems through investigative activities is one of the elements of contextual learning. Contextual learning by solving everyday problems is one aspect of the description of science literacy competencies. The investigation component in guided inquiry is expected to improve students' science literacy. This study aims to determine the effect of guided inquiry learning model on science literacy skills of 4th grade students of SDN Dukuharum Jombang. The population in this study were all 4th grade students of SDN Dukuharum Jombang in semester 1 of the 2022/2023 academic year, while the samples used were classes 4A and 4B. The experimental class and control class each consisted of 20 students. This research is a quantitative study with a quasi-experimental research method with a research design of nonequivalent pretest posttest pretest- posttest control group design. The results of this study indicate that guided inquiry has a significant effect on science literacy skills.